Questions in a Life‐Sized Board Game: Comparing Caregivers' and Children's Question‐Asking across STEM Museum Exhibits. Issue 2 (5th March 2021) - Gaudreau, Caroline; Bustamante, Andres S.; Hirsh‐Pasek, Kathy; Golinkoff, Roberta Michnick
ABSTRACT: Parkopolis, the life‐sized board game, was designed to promote conversation and science, technology, engineering, and mathematics (STEM) learning. We investigated whether this exhibit also prompted questioning. Caregivers' and children's STEM‐related question‐asking was compared between Parkopolis (i.e., experimental group) and a STEM‐themed control exhibit. Groups ( N =  197) of children and caregivers visiting two exhibits in a museum were observed. Observations revealed that caregivers and children asked more mathematical questions in Parkopolis than in the control. Caregivers also asked more spatial questions in Parkopolis. In addition, when all STEM‐related question topics (i.e., mathematical, spatial, and scientific thinking) were combined, children asked more STEM‐related questions in Parkopolis than in the control. Finally, children responded to a higher proportion of caregivers' questions in Parkopolis than in the control. Factors that promoted this question‐asking in Parkopolis, such as signage and the interactive nature of the exhibit, can inform the design of other informal learning spaces to promote question‐asking. Abstract : Lay Abstract : We investigated whether children's and caregivers' questions about math, spatial, and scientific topics could be increased in a museum exhibit specifically designed to promote this type of questioning. We found that both caregivers and children asked more of these questions when playing in Parkopolis, a life‐sized mathematical‐ and spatial‐themed board game, than in a control exhibit. Our findings have implications for how other informal learning spaces can be designed to increase question‐asking and conversation.